Beneficios de la hidrocinesiterapia sobre el estado de salud en gestantes - Paulina Verónica, Culqui Gaibor (2021)
ABSTRACT Hydrokinesitherapy, it refers to execute exercises in an aquatic environment, this therapy that allows to develop and to improve the aerobic and anaerobic capacity of the people who practice it, currently there are multiple studies that refer its benefits regarding health care, since its application focuses on prevention, control and physical rehabilitation, that is the reason about this investigation purpose was to investigate and focus on those benefits on pregnant women population, according their physical and anatomical adaptations of pregnancy, limit exercise practice, which leads to a sedentary lifestyle which has been reflected in different complications during and after it. Through a bibliographic search of topics on pregnancy hydrokinesitherapy, 34 scientific articles were selected, which according their criteria proclaim that they have to grade a score of 6 or more according to the PEDro scale, which are summarized and presented in charts with the information that responds to the research topic, the additional bibliography that did not accomplish a same score or greater than 6 according to the PEDro scale was not discarded, it was integrated into the discussion section according to the contrast of the results achieved. From the selected documentation was possible to verify, that this practice of hydrokinesitherapy in pregnancy allows to control their health status of pregnant women, its practice must be guided by a professional in the area, who guarantees the safety of the pregnant woman treatment. Key words: "Aquatic therapy - Pregnancy", "Hydrotherapy - Pregnancy", "Hydrokinesitherapy - Pregnancy", "Aquatic physical therapy - Pregnancy". Reviewed by: Msc. Adriana Cundar Ruano, Ph.D. ENGLISH PROFESSOR c.c. 1709268534